Validation of the Holmlund-Grooten sub-maximal arm crank ergometer-test for estimating peak oxygen uptake in wheelchair users with Spinal Cord Injury - Tobias Holmlund; Wilhelmus Johannes Andreas Grooten (PLoS ONE, 2026)
Study design Cross-sectional validity study. Objectives To determine the criterion validity, Standard Error of the Measurement (SEM) and Minimal Detectable Change (MDC), of a newly developed submaximal test (Holmlund-Grooten test) for estimating the peak oxygen consumption in wheelchair users with motor-complete Spinal Cord Injury (mcSCI). Settings Outpatient rehabilitation centre in Stockholm, Sweden. Methods Peak and submaximal oxygen uptake (VO 2 ) was measured using indirect calorimetry. A backward linear regression model, including heart rate, power output, and several demographic variables, was used to predict absolute VO 2peak . Results In total, 63 individuals (16 females) with mcSCI were included. The final prediction model included four significant (p < 0.05) variables (sex, injury level, heart rate, power output) that were able to predict absolute VO 2peak (adjusted R 2 = 0.77). The Holmlund-Grooten test showed excellent criterion validity (ICC = 0.88; 95%CI 0.83–0.94), SEM = 0.05 L·min -1 and MDC = 0.13 L·min -1 . No adverse events were reported. We provide an Excel file that calculates VO 2peak based on the Holmlund-Grooten model for males and females and tetra- and paraplegia for clinical use. Conclusion The Holmlund-Grooten test is a valid submaximal test for estimating VO₂ peak in wheelchair users with SCI and can be easily implemented in clinical settings.